Strategi Pengembangan Usaha Mikro Kecil Menengah (UMKM) Berbasis Ekonomi Kreatif di Kecamatan Serang, Kabupaten Serang - Vera Maria; Tesalonika Situmeang; Robbi Fito Ardana (Institut Nalanda, 2024)
This research aims to examine strategies for developing creative economy-based micro, small, and medium enterprises (MSMEs) in Serang District, Serang Regency. The research method used is qualitative, involving observation, interviews, and documentation, as well as analyzing the SWOT matrix to identify strengths, weaknesses, opportunities, and threats in developing MSMEs in the region. Informants consisted of various parties, including the sub-district head, MSME actors, academics, and government agencies. The research results show that creative economy-based MSMEs in Serang District face a number of challenges, such as limited capital, raw materials, production equipment, and limited market access. The recommended development strategy is the SO (growth) strategy, which prioritizes the use of internal strengths to increase competitive advantage, product diversification, strengthening cooperation between MSMEs, improving product quality, and more aggressive marketing. By implementing these strategies, it is hoped that MSMEs in Serang District can increase their contribution to regional economic development